PENERAPAN SISTEM KEAMANAN BERBASIS MIKROKONTROLER VIA PONSEL PADA MOTOR HONDA VARIO 110 CC - Anam, Khoirul; Setiawan, Sofiyan; Khaerudin, Muhammad (Universitas Muhammadiyah Pekajangan Pekalongan, 2019)
AbstractEach motor vehicle must have a security system. Modern Motorcycle safety system is the usual solution by the owners of motorists to ensure the safety of its vehicles. On the other hand, along with the development of technology, Handphone is one of technology that has various facilitiesÂ withBluetooth and Android application. By creating an Android application to install on the phone andadding a little bit of microcontroller based. The function of mobile phone not only for means of communication tools via voice or SMS but also can be used as a safety device on motorcycles. Keywords : Security system, Microcontroller